Effects of stripping foetal membranes on Pregnancy duration and rate of Induction. - Thirukumar, M (My University, 2005)
Objective of the study was to determine the effect of sweeping of the foetal membrances at 39 weeks of period of amenorrhoea on duration of pregnancy, onset of labour and mode of delivery. A randomized controlled study, 216 nulliparous women with uncomplicated pregnancy were randomly allocated at 39 weeks of period of amenorrhoea to receive sweeping of membrane